Does remote work improve or impair firm labour productivity? Longitudinal evidence from Portugal - Monteiro, Natália P. (2019)
Whether or not the use of remote work increases firm labour productivity is theoretically ambiguous. We use a rich and representative sample of Portuguese firms, and within-firm variation in the policy on remote work, over the period 2011-2016, to empirically assess the causal productivity effect of remote work. Our findings from estimations of models with firm fixed effects suggest that the average productivity effect of allowing remote work is significantly negative, though relatively small in magnitude. However, we also find a substantial degree of heterogeneity across different categories of firms. In particular, we find evidence of opposite effects of remote work for firms that do not undertake R&D activities and for firms that do, where remote work has a significantly negative (positive) effect on labour productivity for the former (latter) type of firms. Negative effects of remote work are also more likely for small firms that do not export and employ a workforce with a below-average skill level.